Poziom A
a) 4*2 -8= 8-8=0
b) 2/ 3*3-2 = 2/7
c) 3^2+5*3/6 = 9+15/2= 24/2= 12
d) 2*4+2^2= 8+4=12
e) 2^2 - 2^3 = 4 -8 = -4
f) 3*4 - 1 = 12 -1= 11
g) 2/5*(7+3)^2= 2/5*100= 200/5=40
h) 5(5+2)= 5* 7= 35
i) 0
Poziom B
a) 5*(-3) + (-3)^2 = (-15) + 9 = - 6
b) 4,5+2(-3)^2/3 = 4,5+ 2*9/3 = 4,5 + 18/3= 22,5/3 = 7,5
c) (-2)^2 - (-2)^2 = 4 - 4 = 0
d) 3(-1)^2+2(-1)= 3*1+ (-2) = 1
e)-7/8-4(-1)= -7/ 8- (-4) = -7/12
f) 2(4(-1)+1) -5 = 2((-4)+1)-5= 2*(-3)-5= -6-5= -11
g) -4( (-4)+3)= -4*(-1)= 4
h)3/4 ( (-6) -2)^2 = 3/4* (-8)^2= 3/4 * 64 = 0,75 *64= 48
i) 4*(-2) -2/11 = -8-2/11= -10/11